No association between VAPB mutations and familial or sporadic ALS in Sweden, Portugal and Iceland. Issue 7 (December 2013) - Ingre, Caroline; Pinto, Susana; Birve, Anna; Press, Rayomand; Danielsson, Olof; de Carvalho, Mamede; Guđmundsson, Grétar; Andersen, Peter M.
Abstract: Linkage analysis in Brazilian families with amyotrophic lateral sclerosis (ALS) revealed that a missense mutation p.Pro56Ser in a conserved gene VAMP-associated protein type B and C ( VAPB ) cosegregates with disease. Blood samples were studied from 973 Swedish, 126 Portuguese and 19 Icelandic ALS patients, and from 644 control subjects. We identified five VAPB mutations, two of which are novel, in 14 Swedish ALS patients and in nine control individuals from Sweden and Portugal. The 14 patients with VAPB mutations all carried a diagnosis of sporadic ALS. Mutations were also found in healthy adult relatives. The p.Asp130Glu VAPB mutation was also found in two patients from an Icelandic ALS family, but the mutation did not cosegregate with disease. All patients were instead found to be heterozygous for a p.Gly93Ser SOD1 mutation. There were no clinical differences between them, suggesting that the p.Asp130Glu VAPB mutation is unrelated to the disease process. In conclusion, the VAPB mutations were as frequent in control individuals as in patients. This observation, in combination with the finding of several healthy relatives carrying the VAPB mutations and no ancestors with ALS disease, suggests that it is unlikely that these VAPB mutations are pathogenic.